2013 Africon 2013
DOI: 10.1109/afrcon.2013.6757693
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prior learning on mathematics performance at secondary level

Abstract: This research study was triggered by the relatively low percentage of students who successfully study mathematics at the Higher School Certificate (HSC )level. While pass rate in mathematics averages 76% at primary level, it remains a concern that only around 42% of School Certificate (SC) students get a good grade (distinction or credit) in that subject. Causes are multifaceted but this study particularly sought to investigate the effects of prior learning achievement at the Certificate of Primary Education (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…But a grade A at CPE does not automatically lead to a grade A at SC, such that, only around one third of those who scored a grade A at CPE could manage to get a similar grade at SC. This is very close to the theoretical pattern developed by Appavoo et al (2013) (Table 1) where it depicted that only around one third (1894/5494) of those who got a grade A at CPE, obtained a similar grade at SC.…”
Section: Findingsupporting
confidence: 88%
See 2 more Smart Citations
“…But a grade A at CPE does not automatically lead to a grade A at SC, such that, only around one third of those who scored a grade A at CPE could manage to get a similar grade at SC. This is very close to the theoretical pattern developed by Appavoo et al (2013) (Table 1) where it depicted that only around one third (1894/5494) of those who got a grade A at CPE, obtained a similar grade at SC.…”
Section: Findingsupporting
confidence: 88%
“…In a previous study (Appavoo et al, 2013) it was found that although good grades at primary level were not a guarantee of good grades at secondary level, yet the majority of students who did well at the latter level were those who obtained good grades at the primary level. In a nutshell, this study reveals that:…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This study purports that students are ready to embrace ICT for pedagogical gains. We are also aware that teachers' perception and beliefs of the merits of ICT are on the positive side [8]. The schools in Mauritius therefore have two of the most important ingredients to make ICT integration a successful learning endeavour.…”
Section: Conclusion and Recommendationmentioning
confidence: 99%
“…We are therefore at a major crossroad where we hope to see ICT reshaping the learning abilities of students. This research is of particular interest as Mathematics learning disabilities are rampant among too many students [8] and it is worth investigating if ICT can offer prospective avenues to remedy the situation.…”
Section: Introductionmentioning
confidence: 99%